Crónica de una migración anunciada : las migraciones de retorno a las raíces de argentinos en Galicia (España) a principios del siglo XXI - Sofía Laíz Moreira (Amnis)
This paper presents an analysis of those factors that have determined the migration of families proceeding from different locations in Buenos Aires Province, Argentina, migrating to Galicia’s region, in Spain, in the first years of 21st century. The historical moment where these migrations took place described a socio-political scenario of extreme convulsion in this austral country. After trying to understand the historical elements that explain migrations between both social spaces, this paper presents the results of a research work that searched for understanding the migration projects of sixteen family’ groups, paying special attention to their intergenerational social mobility strategies by migration. To do so, a tridimensional analysis of macro, meso and micro sociological determinants has been developed, taking into account the fundamental influence of the social contex variable on migrants’ social integration pathways.